Flexible work and the family - Abendroth, Anja-Kristin; Lükemann, Laura (Contemporary perspectives on family research, 2023)
Building upon the recent global escalation of the remote work phenomenon, Flexible Work and the Family provides timely insights into flexible work's implications for the increasingly blurred work-life divide.